Ethical Decision Making In Higher Education Institutions - Thongchana, Panumas; Thummachote, Ravipa (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims to study the ethical decision-making approaches of academics in institutions of higher education when they encounter ethical conflicts regarding the determination of academic positions. Interpretative phenomenological analysis, a form of qualitative research, together with document research are used. Data is further collected from in-depth interviews with a total of 17 academics from institutions of higher education. The study reveals that ethical decision making in institutions of higher education occurs, for the most part, without a structure. This is due to the complexity of the situations and the lack of clarity about the problems. As a result, it is not possible to determine in advance the decision-making approaches to address such ethical problems. Factors that impact the ethical decision-making approaches include personal characteristics in terms of the prior experiences of decision makers and the organizational culture. Article history: Received 20 March 2023 Revised 2 May 2023 Accepted 3 May 2023 SIMILARITY INDEX = 0.00 %